Terricolous Lichens in India Volume 1: Diversity Patterns and Distribution Ecology - Rai, Himanshu; Upreti, Dalip K. (Springer New York : Imprint: Springer, 2014)
Terricolous lichens, a habitat specialist group of lichens play a vital role in maintenance and ecological stability of soil crusts with reference to their physical stability, hydrology and growth of soil microflora. Terricolous lichens in Indian lichenological studies haven't been taken up as a functional group.   Terricolous Lichens in India, Volume 1: Diversity Patterns and Distribution Ecology is the first ever publication dealing with soil lichens of India. Divided into five chapters, this volume discusses the lichenological researches in India with reference to terricolous lichens, the altitudinal distribution patterns of terricolous lichens, comparative assessment of distribution with global patterns, and the photobiont diversity and influence of novel molecular clades of photobiont in determining ecological preferences of soil lichens in India.   Written by experts in the field and supplemented with numerous photographs, Terricolous Lichens in India, Volume 1: Diversity Patterns and Distribution Ecology is a comprehensive resource that addresses the major drivers of terricolous lichens distribution in India.